2022
DOI: 10.1021/jacs.1c11341
|View full text |Cite
|
Sign up to set email alerts
|

Temperature Regulates Stability, Ligand Binding (Mg2+ and ATP), and Stoichiometry of GroEL–GroES Complexes

Abstract: Chaperonins are nanomachines that harness ATP hydrolysis to power and catalyze protein folding, a chemical action that is directly linked to the maintenance of cell function through protein folding/refolding and assembly. GroEL and the GroEL−GroES complex are archetypal examples of such protein folding machines. Here, variable-temperature electrospray ionization (vT-ESI) native mass spectrometry is used to delineate the effects of solution temperature and ATP concentrations on the stabilities of GroEL and GroE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
33
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 28 publications
(36 citation statements)
references
References 76 publications
3
33
0
Order By: Relevance
“…A recent example reported by Walker et al revealed remarkable effects of native MS buffers, AmAc and EDDA, on the conformation and stabilities of the GroEL tetradecamer. 42 The protein complexes of C-reactive protein (CRP of ∼115 kDa), pyruvate kinase (PK of ∼237 kDa), and glutamate dehydrogenase (GDH of ∼334 kDa (experimental)) were studied using mixed buffers containing various concentrations of AmAc and TEAA, and the effects of nESI (nano-ESI) emitter potentials were also examined. Higher concentrations of TEAA and higher emitter potentials at each TEAA concentration decreased the Z avg for all proteins.…”
Section: ■ Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent example reported by Walker et al revealed remarkable effects of native MS buffers, AmAc and EDDA, on the conformation and stabilities of the GroEL tetradecamer. 42 The protein complexes of C-reactive protein (CRP of ∼115 kDa), pyruvate kinase (PK of ∼237 kDa), and glutamate dehydrogenase (GDH of ∼334 kDa (experimental)) were studied using mixed buffers containing various concentrations of AmAc and TEAA, and the effects of nESI (nano-ESI) emitter potentials were also examined. Higher concentrations of TEAA and higher emitter potentials at each TEAA concentration decreased the Z avg for all proteins.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Monomeric proteins have been extensively studied via ESI-MS; therefore, we have chosen to conduct these experiments on protein complexes, which offer more diverse and less well-studied responses to charge reduction conditions. A recent example reported by Walker et al revealed remarkable effects of native MS buffers, AmAc and EDDA, on the conformation and stabilities of the GroEL tetradecamer . The protein complexes of C-reactive protein (CRP of ∼115 kDa), pyruvate kinase (PK of ∼237 kDa), and glutamate dehydrogenase (GDH of ∼334 kDa (experimental)) were studied using mixed buffers containing various concentrations of AmAc and TEAA, and the effects of nESI (nano-ESI) emitter potentials were also examined.…”
Section: Introductionmentioning
confidence: 99%
“…Mg 2+ ions are essential for the binding of ATP to proteins and K + ions have been known as strong activators of ATPase activity. In previous work we have shown that the Mg 2+ concentration impacts the stoichiometry of GroES binding to GroEL 21 (also see Figure S4 ), which illustrates the importance of Mg 2+ concentration for proper functioning of the GroEL nanomachine. Lorimer et al have shown that K + ions are necessary for the modulation of the ATPase mechanism of GroEL.…”
Section: Resultsmentioning
confidence: 52%
“…1 While the structure, dynamics, and ATP binding of GroEL has been extensively investigated, [8][9][10][11][12][13][14][15][16][17][18][19][20] we recently reported results using native mass spectrometry (nMS) that reveal new insights about stability and stoichiometry of GroEL-ATP/GroES interactions. 21 Using variable-temperature electrospray ionization (vT-ESI) we found that GroEL-ATP binding was temperature and ATP-concentration dependent, indicating that the thermodynamics of this vital interaction for the GroEL nanomachine might reveal new information as to how the GroEL nanomachine operates. This could provide new strategies for analysis of thermodynamics of individual binding reactions for multi-dentate systems which is especially challenging and remains difficult to achieve with current methods.…”
Section: Introductionmentioning
confidence: 99%
“…It has been used to analyze a vast number of proteins and oligonucleotides and has provided great insight into their structural and functional characteristics, which could not be readily obtained by other techniques . For example, native MS has been used to investigate peptide interactions, DNA thermodynamics, , antibody binding, chaperones, , protein aggregation, , as well as very large biomolecular complexes such as ribosomes and intact viruses . This is due to the development of electrospray ionization (ESI), which has allowed researchers to transfer biomolecules from solution into the gas phase without inducing significant disruptions to their structure.…”
Section: Introductionmentioning
confidence: 99%